Alternative diets based on rice bran and flour for experimental model nutrition - Drosophila melanogaster (Research, Society and Development, 2023)
This work aims to elaborate diets based on rice by-products for the nutrition of Drosophila melanogaster and to verify the acceptability of the experimental model. To identify the nutritional composition of the samples, chemical analyzes were performed on: rice polishing bran (FPA); rice burnished bran (FBA); coarse cornmeal (FMG) and medium cornmeal (FMM). The composition of rice flour was obtained from the literature. The diets were developed with the ingredients used in the standard diet, replacing corn flour with rice by-products in different proportions in each of the diets. In the laboratory, the consistency of the diets and food consumption were tested. In the chemical analyses, the following results were obtained: higher ash, lipid, protein and dietary fiber content in rice bran compared to corn flour; Higher amount of carbohydrates in the rice flour sample, followed by FMM, FMG, FPA and FBA; Only the caloric value of FBA differed statistically. Regarding the diets: The protein content of the FFA and standard diets were similar, the FA diet had higher values; The FA and FFA diets exhibited a higher amount of lipids; The FA and FFA diets had less carbohydrates; The caloric value remained similar in the three diets. In the food consumption test, there was no statistical difference between the diets. The results of the study provide evidence that it is possible to develop diets based on rice by-products, with nutritional quality and that there was acceptance of the diets by the experimental model.